Knowledge of the perception of cybersecurity in the students of the school of economics of the University of Costa Rica in their daily lives with a focus on social network - Castro-López, María Paz (2024)
The objective of this research is to carry out an exploratory analysis in relation to the knowledge that students of the UCR Economics course have regarding their use of Cybersecurity in social networks in their personal accounts and how to access them properly. Then a quick guide is proposed that contains a series of steps that are recommended to increase knowledge of the subject and achieve improvements in the use of social networks, secure access and impersonation techniques that can occur in these networks.